The effect of maize vitreousness and a starch binder on in vitro fermentation parameters and starch digestibility in dairy cows - Van Zyl, Johan Hendrik Combrink (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.